Production of titanium oxide nano wires with bundle structure using single anodic process - Mustafa Hashim; Reem Saadi Khaleel (Kuwait Journal of Science)
In a single process, the surface of Ti was transformed into titanium oxide nanowires (TNWs) at room temperature. The rapid breakdown anodizing method (RBA) of producing deposited spherical nanoparticles was modified. Instead, TNWs attached to the Ti metal base were formed. To slow down the reactions of these processes, 25,50, and 75wt % glycerol were added separately to the anodizing solution of RBA. The results of the X-ray diffraction (XRD) tests revealed the amorphous structure of the formed TNWs for all samples. The produced TNWs had the shape of micro bundles with nanowires. Their diameters were less than 50 nm, as shown by scanning electron microscope (SEM) images. The prevalence of titania bundles was more intense when a lower amount of glycerol was used. The tallest length of the nanowires decreased from 32μm to 8μm with the increase of glycerol; so by using a suitable electrolyte solution, the anodizing process can be effective for controlling the size of TNWs. The decrease in atomic percent oxygen with increasing glycerol was confirmed by energy dispersion X-ray (EDX) spectra.